Incidental findings on brain MR imaging of asymptomatic term neonates in the Developing Human Connectome Project - Carney, Olivia (EClinicalMedicine, 2021)
BACKGROUND: Interpretation of incidental findings on term neonatal MRI brain imaging can be challenging as there is a paucity of published normative data on asymptomatic term neonates. Reporting radiologists and clinicians need to be familiar with these incidental findings to avoid over-investigation and misinterpretation particularly in relation to neurodevelopmental outcome. This study aimed to determine the prevalence of incidental findings in a large group of asymptomatic term neonates participating in the Developing Human Connectome Project (dHCP) who were invited for neurodevelopmental assessment at 18 months. METHODS: We retrospectively reviewed MRI brain scans performed on 500 term neonates enrolled in the dHCP study between 2015 and 2019 with normal clinical examination. We reviewed the results of the Bayley Scales of Infant and Toddler Development (Bayley III) applied to participants who attended for neurodevelopmental follow-up at 18 months. Scores considered “delayed” if <70 on language, cognitive or motor scales. FINDINGS: Incidental findings were observed in 47% of term infants. Acute cerebral infarcts were incidentally noted in five neonates (1%). More common incidental findings included punctate white matter lesions (PWMLs) (12%) and caudothalamic subependymal cysts (10%). The most frequent incidental finding was intracranial haemorrhage (25%), particularly subdural haemorrhage (SDH). SDH and PWMLs were more common in infants delivered with ventouse-assistance versus other delivery methods. Neurodevelopmental results were available on 386/500 (77%). 14 infants had a language score < 70 (2 SD below the mean). Of the 386 infants with neurodevelopmental follow up at 18 months, group differences in motor and language scores between infants with and without incidental findings were not significant (p = 0·17 and p = 0·97 respectively). Group differences in cognitive scores at 18 months between infants with (median (interquartile range) -100 (95–105)) and without (100 (95–110)) incidental findings were of small effect size to suggest clinical significance (Cliff's d = 0·15; p<0·05). INTERPRETATION: Incidental findings are relatively common on brain MRI in asymptomatic term neonates, majority are clinically insignificant with normal neurodevelopment at 18 months. FUNDING: This work was supported by the European Research Council under the European Union's Seventh Framework Programme (FP7/20072013/ERC grant agreement no. [319456] dHCP project), by core funding from the Wellcome/EPSRC Centre for Medical Engineering [WT203148/Z/16/Z] and by the National Institute for Health Research (NIHR) Biomedical Research Centre based at Guy's and St Thomas’ NHS Foundation Trust and King's College London and/or the NIHR Clinical Research Facility. The views expressed are those of the authors and not necessarily those of the NHS, the NIHR or the Department of Health and Social Care.